Pendekatan “Real Option” Dalam Valuasi Aset Jalan Tol Trans Sumatera - Muhammad Rifqy; Zaäfri Ananto Husodo (Universitas Serang Raya, 2024)
Sumatra Island is the locomotive of Indonesia's economic development in the western region, so the development of the economy in Sumatra Island is one of the conditions for the sustainability of the economy in western Indonesia and the Indonesian economy in general. Therefore, if development in Sumatra Island stagnates, the development of the surrounding areas will also be hampered. In order to improve the smooth movement of goods and people and distribution on the island of Sumatra, the central government encourages the construction of the Trans Sumatra Toll Road (